Pengaruh Brand Image dan Brand Trust Terhadap Repurchase Intention Pada Pengguna Aplikasi Shoope di Kota Banjarmasin - jinggasukmana; Ilisa Fajriyati; Syahrani Syahrani (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the influence of Brand image and Brand Trust on the Repurchase intention of Shopee app users in Banjarmasin City, both partially and simultaneously. The study employs a quantitative approach using a survey method. The research population consists of Shopee app users in Banjarmasin City who have made a purchase through the Shopee app. The sample comprises 100 respondents selected using the purposive sampling technique. Data collection was conducted via online questionnaires. Data analysis includes descriptive statistics, validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, the coefficient of determination (R²), t-tests, and F-tests, utilizing IBM SPSS Statistics version 23 software.The results indicate that Brand image has a positive and significant influence on the Repurchase intention of Shopee app users in Banjarmasin City. Brand Trust also has a positive and significant influence on Repurchase intention. Furthermore, Brand image and Brand Trust simultaneously exert a positive and significant influence on the Repurchase intention of Shopee app users in Banjarmasin City. These findings indicate that a superior Shopee Brand image and higher levels of consumer trust in the Shopee brand increase the likelihood of consumers making repeat purchases through the Shopee app.